The stress-related, rhizobial small RNA RcsR1 destabilizes the autoinducer synthase encoding mRNA sinI in Sinorhizobium meliloti. Issue 5 (3rd May 2016) - Baumgardt, Kathrin; Šmídová, Klára; Rahn, Helen; Lochnit, Günter; Robledo, Marta; Evguenieva-Hackenberg, Elena
ABSTRACT: Quorum sensing is a cell density-dependent communication system of bacteria relying on autoinducer molecules. During the analysis of the post-transcriptional regulation of quorum sensing in the nitrogen fixing plant symbiont Sinorhizobium meliloti, we predicted and verified a direct interaction between the 5'-UTR of sinI mRNA encoding the autoinducer synthase and a small RNA (sRNA), which we named RcsR1. In vitro, RcsR1 prevented cleavage in the 5'-UTR of sinI by RNase E and impaired sinI translation. In line with low ribosomal occupancy and transcript destabilization upon binding of RcsR1 to sinI, overproduction of RcsR1 in S. meliloti resulted in lower level and shorter half-life of sinI mRNA, and in decreased autoinducer amount. Although RcsR1 can influence quorum sensing via sinI, its level did not vary at different cell densities, but decreased under salt stress and increased at low temperature. We found that RcsR1 and its stress-related expression pattern, but not the interaction with sinI homologs, are conserved in Sinorhizobium, Rhizobium and Agrobacterium. Consistently, overproduction of RcsR1 in S. meliloti and Agrobacterium tumefaciens inhibited growth at high salinity. We identified conserved targets of RcsR1 and showed that most conserved interactions and the effect on growth under salt stress are mediated by the first stem-loop of RcsR1, while its central part is responsible for the species-specific interaction with sinI . We conclude that RcsR1 is an ancient, stress-related riboregulator in rhizobia and propose that it links stress responses to quorum sensing in S. meliloti.